Theoretical approach to the study of vibrational effects on strong field ionization of molecules with alignment-dependent tunneling ionization rates - 张美霞 闫冰 杨玉军 罗嗣佐 朱瑞晗 杨雪 丁大军 (Chinese physics B, 2015)
The tunneling ionization rates of vibrationally excited N2 molecules at the ground electronic state are calculated using molecular orbital Ammosov–Delone–Krainov theory considering R-dependence. The results show that molecular alignment significantly affects the ionization rate, as the rate is mainly determined by the electron density distribution of the highest occupied molecular orbital. The present work indicates that the ratios of alignment-dependent rates of different vibrational levels to that of the vibrational ground level increase for the aligned N2 at the angle θ = 0？, and suggests that the alignment-dependent tunneling ionization rates can be used as a diagnostics for the influence of vibrational excitation on the strong field ionization of molecules.